2011
DOI: 10.1007/s12013-011-9153-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP-Activated Protein Kinase Contributes to Doxorubicin-Induced Cell Death and Apoptosis in Cultured Myocardial H9c2 Cells

Abstract: Despite its potent antitumor effect, clinical use of Doxorubicin is limited because of serious side effects including myocardial toxicity. Understanding the cellular mechanism involved in this process in a better manner is beneficial for optimizing Doxorubicin treatment. In the current study, the authors focus on the AMP-activated protein kinase (AMPK) in the said process. In this study, the authors discovered for the first time that Doxorubicin induces AMPK activation in cultured rat embryonic ventricular myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 57 publications
6
87
0
Order By: Relevance
“…Notably, we observed that doxorubicin might activates AMPK at initial stage (Ͻ4 h), but it did not induce cell apoptosis under short time treatment under our current conditions (Fig. 7, A and B), similar results were reported by other groups (43,44), which might be due to a transient increase in reactive oxygen species levels after adding doxorubicin (44). But the detailed mechanism of this transient activation of AMPK by doxorubicin is unknown, which warrants further investigation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Notably, we observed that doxorubicin might activates AMPK at initial stage (Ͻ4 h), but it did not induce cell apoptosis under short time treatment under our current conditions (Fig. 7, A and B), similar results were reported by other groups (43,44), which might be due to a transient increase in reactive oxygen species levels after adding doxorubicin (44). But the detailed mechanism of this transient activation of AMPK by doxorubicin is unknown, which warrants further investigation.…”
Section: Discussionsupporting
confidence: 87%
“…However, the role of AMPK in doxorubicin-induced apoptosis is a matter of debate. For example, Chen et al (44) and Ji et al (43) have described that doxorubicin-induced early AMPK (Ͻ6 h) contributes to cellular death (Ͼ16 h) in cultured H9C2 cells or in cancer cell lines. Whether or not doxorubicin-induced AMPK activation at early stage (Ͻ6 h) is responsible for late stage apoptosis is unknown because prolonged incubation of doxorubicin inhibits AMPK.…”
Section: Ampk␣1mentioning
confidence: 99%
“…Detailed procedures can be found in other studies. 37,38 Briefly, the cells were lysed and the cell lysates were overlaid and incubated in microtiter plate modules coated with anti-Histone antibody. Samples were then incubated with anti-DNA peroxidase followed by color development with ABTS substrate.…”
Section: Caspase-3 Activity Assaymentioning
confidence: 99%
“…In contrast to the well established role of AMPK in metabolic regulation, there is no consensus on its role or the underlying mechanism under genotoxic stress. Some reports have demonstrated that AMPK is activated in H9c2 (14) and cancer cell lines (15) by doxorubicin. In contrast, AMPK is inhibited by long term treatment of doxorubicin in mouse embryonic fibroblasts (MEFs) (16).…”
Section: Doxorubicin Is One Of the Most Widely Used Anti-cancer Drugsmentioning
confidence: 99%